A collagen fiber material and its preparation method and application
By combining salting and self-assembly technology, collagen is precipitated in fiber state and self-assembled, solving the problem of introducing toxic crosslinking agents when collagen materials improve mechanical properties and enzymatic resistance, and achieving high-strength and enzymatic resistance fiber collagen materials.
Patent Information
- Application Number
- CN202510128481.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-05
AI Technical Summary
In the prior art, collagen materials are prone to introduce toxic crosslinking agents when improving mechanical properties and enzymatic properties, and the degree of crosslinking is difficult to control, which affects the safety and use function of the material.
By combining protein salting out and collagen self-assembly technology, a special salting out process is used to controllably precipitate collagen in the fiber state, and through self-assembly and shaped, fiber collagen materials with high concentration, high mechanical strength and strong enzymatic resistance are obtained.
The high mechanical strength and enzymatic resistance of collagen materials are achieved without adding crosslinking agents, avoiding the problem of material gelation and high moisture content, and are suitable for in vivo implantation filling.
Smart Images

Figure CN119593080B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of organic polymer compound processing, and also to the field of medical material technology, in particular to a collagen fiber material and a preparation method and application thereof. Background Art
[0002] As an implant material, collagen needs to have sufficient strength and elasticity to support the load of tissues, and at the same time, it needs to be able to resist degradation by enzymes in the body and prolong the effective use time of the implanted collagen material. By cross-linking and modifying the collagen material, the physical and chemical properties of the material can be improved. However, the use of chemical cross-linking agents may introduce toxic substances, affecting the safety of the material; at the same time, the degree of cross-linking is difficult to control, causing the material to become brittle, reducing elasticity and flexibility, and affecting the material's use function.
[0003] Under the premise of non-crosslinking, collagen can have the above physical and chemical properties by increasing the collagen concentration, increasing the mechanical strength of the collagen material and improving its resistance to enzymatic hydrolysis. Protein salting out is a commonly used concentration method, but it is essentially a large number of single-molecule aggregates, and the material's resistance to enzymatic hydrolysis and mechanical properties are insufficient. Since collagen molecules are special rod-shaped molecules, they tend to aggregate quickly after salting out. It is not easy to obtain materials with high concentration, high strength and strong resistance to enzymatic hydrolysis.
[0004] Collagen materials have the physiological activity of self-assembly under physiological conditions. Collagen self-assembly refers to the process in which collagen molecules automatically aggregate and arrange to form a higher structure under specific environmental conditions. This can effectively improve the physical and chemical properties of the material. However, the self-assembled collagen materials usually form a gel-like structure, resulting in an increase in water content, poor mechanical strength, and insufficient resistance to enzymatic hydrolysis, making them unsuitable for implant filling functions.
[0005] In order to improve the mechanical properties and resistance to enzymolysis of collagen, the prior art considers chemical cross-linking of collagen materials. Chinese Patent 202410361047.4 discloses glutaraldehyde cross-linked collagen fibers and methods for their preparation and application. The cross-linked material obtained has improved resistance to enzymolysis, but the residual glutaraldehyde may cause unknown adverse reactions in the body. There is a problem of residual cross-linking agent in the cross-linked collagen material, which affects the safety of the material; at the same time, the degree of cross-linking is difficult to control, which may cause the material to be over-cross-linked, hardened and brittle, and unusable; chemical cross-linking will damage the biological activity of collagen and affect cell attachment and proliferation.
[0006] In order to improve the physicochemical properties of collagen materials without adopting a cross-linking scheme, the prior art can increase the physicochemical properties of materials by increasing the collagen concentration through the method of salting out to aggregate the molecules. In the field of collagen material processing and preparation, the application of the salting out process is a purification step in the collagen processing process. The collagen precipitate is collected by salting out to remove small molecule proteins and impurities in the solution. For example, Chinese patent CN200510028759.1 discloses a preparation process for collagen sponge, in which the collagen precipitate in the collagen crude extract is obtained by salting out, and the collagen is purified by subsequent re-dissolution. However, the essence of protein salting out is a large number of single-molecule aggregates, and the material's resistance to enzymatic hydrolysis and mechanical properties are insufficient. Since collagen molecules are special rod-shaped molecules, they are easily aggregated into agglomerates quickly after salting out, resulting in uneven materials; it is not easy to obtain materials with high concentration, high strength, and strong resistance to enzymatic hydrolysis.
[0007] In addition, there are also methods in the prior art to improve the physical and chemical properties of materials by self-assembling collagen molecules to achieve molecular rearrangement. However, the self-assembled collagen material usually forms a gel-like structure, which leads to an increase in water content, poor mechanical strength, and insufficient resistance to enzymatic hydrolysis, so it is not suitable for implantation and filling functions. For example, Chinese patent 201410229105.4 discloses a method for self-assembly of aquatic collagen into fibers, and a collagen hydrogel is prepared. However, this type of material is in a gel state, has a high water content, and poor mechanical strength, and cannot be used for in vivo implantation. Summary of the invention
[0008] One of the invention purposes of the present invention is to address the problems in the prior art that in order to improve the mechanical properties and resistance to enzymolysis of collagen, a cross-linking agent needs to be introduced into the collagen material; the precipitation of non-cross-linked collagen materials is uncontrollable, and the resistance to enzymolysis and mechanical properties are insufficient. A method for preparing a fibrous collagen material with high concentration, high mechanical strength and strong resistance to enzymolysis is established; protein salting out and collagen self-assembly are organically combined, and collagen is controllably precipitated in a fibrous state through a special salting out process, and the obtained fibrous collagen is self-assembled and finalized through a special process. This not only avoids the problem of insufficient material performance in ordinary protein salting out, but also solves the problem of gelling and high water content caused by general collagen self-assembly.
[0009] One purpose of the present invention is to introduce a dispersant into the process of collagen salting out to solve the problem that collagen molecules are easy to aggregate into agglomerates, and control the process so that collagen is precipitated in the form of fibers and exists stably. At the same time, self-assembly is continuously introduced to make the collagen molecules further self-assemble in the state of high fiber aggregation, thereby improving the mechanical strength and resistance to enzymolysis of the material.
[0010] One of the inventive objectives of the present invention is to provide a material which is suitable for implantation and filling in vivo and whose implantation effect can be maintained durably and effectively.
[0011] In a first aspect, the present application provides a collagen fiber material and a preparation method thereof:
[0012] A collagen fiber material and a preparation method thereof, comprising the following preparation steps:
[0013] S1: adding polyol to the acidic collagen solution and stirring to form a mixed solution, wherein the concentration of the polyol in the mixed solution is 35-45 mg / mL;
[0014] Then, a saturated sodium chloride solution is slowly poured into the mixed solution for salting out, while maintaining uniform directional stirring, and the final sodium chloride concentration in the solution is 1.2-2.5 M, and the salting out process is carried out at a low temperature;
[0015] S2: taking the collagen precipitated in step S1 and transferring it to a dispersion solution, wherein the dispersion solution is a 1-1.2 M sodium chloride aqueous solution to which 20-40 mg / mL of a dispersant is added, and the pH is adjusted to 3-4 to obtain a mixed solution;
[0016] S3. Slowly inject an alkaline solution into the solution obtained in step S2 to adjust the pH to 6.5-7.5; then add water to the system to dilute the sodium chloride concentration to 0.1-0.3 M, heat the water bath to 37-39 °C, and let stand for 2-3 h;
[0017] S4: Take out the precipitated collagen fibers, wash with physiological saline, and concentrate them after centrifugation to obtain the final collagen fiber material.
[0018] Furthermore, the pH value of the acidic collagen solution in step S1 is 2-4.
[0019] Furthermore, the collagen in the acidic collagen solution in step S1 includes any one or more combinations of type I collagen, type II collagen, and type III collagen; and the concentration of collagen in the acidic collagen solution is 3-10 mg / mL.
[0020] Furthermore, the polyol includes any one or more combinations of mannitol, sorbitol, xylitol, glycerol, maltitol and isomalt.
[0021] The addition of polyols can improve the uniformity and dispersibility of the collagen salting-out process and avoid the blocky salting-out precipitation of collagen; the combination of polyols with low temperature and appropriate directional uniform stirring can evenly precipitate collagen and grow it into collagen fibers during the shearing process.
[0022] Polyols, especially mannitol, have good antioxidant and osmotic stability, which can effectively protect the triple helix structure in the collagen solution and prevent it from degradation or denaturation; this is particularly significant in an acidic environment. Polyols, especially mannitol, are insensitive to changes in temperature and acid-base environment and can stably maintain the collagen dispersion effect.
[0023] Compared with other dispersants, polyols have better compatibility and stability with collagen. Short peptides may have poor stability in acidic environments and may undergo further hydrolysis, affecting their functions. Mannitol can effectively reduce the aggregation tendency of collagen and form a uniform dispersion system by changing the osmotic pressure and surface activity of the solution. Compared with short peptides and quaternary ammonium salts, mannitol is not easy to compete with the charged groups on the surface of collagen and can better maintain its natural properties. Mannitol itself has stable chemical properties and is not easy to react with other components in the collagen solution (such as acidic groups), which does not affect the activity and function of collagen. Short peptides will competitively bind to the active sites of collagen and affect its function. Quaternary ammonium salts have positively charged characteristics and may produce a charge shielding effect in an acidic environment, affecting the interaction between collagen and other components.
[0024] In this application, a dispersant is first added, and then a sodium chloride solution is added for salting out. The purpose is to make the dispersant between collagen molecules during the salting out process and ease the aggregation process of collagen molecules, which is conducive to the precipitation of fibrous collagen in the subsequent directional uniform stirring process. The dispersant can ensure that the collagen is slowly dispersed and uniformly fibrous. If a sodium chloride solution is first added to the collagen solution for salting out, the collagen molecules in the solution will quickly gather and precipitate around the droplets of high-concentration sodium chloride solution to form granular inclusions. After the dispersant is added, uniform collagen fibrous precipitation can no longer be obtained, but agglomerated block precipitation; similarly, a dispersant and a saturated sodium chloride solution cannot be added at the same time.
[0025] If polyol is not used in step S1, the collagen obtained in the subsequent salting-out process will be a non-uniform precipitate of clumps, and fibrous collagen cannot be precipitated. If a dispersant is not used in step S2, the speed of the collagen self-assembly process in step S3 is uncontrollable, resulting in non-uniform rapid self-assembly, and obtaining a gel-like product instead of fibrous collagen. The steps of the present application are interrelated and synergistic in performance, thereby obtaining collagen fibers with high mechanical properties and resistance to enzymatic hydrolysis.
[0026] Self-assembly in the solution state of the present application refers to the aggregation of free single collagen molecules in the solution state, and regular rearrangement to form fibers. In this process, since the collagen molecules are aggregated into fibers from the free state, there are a large number of water molecules between the molecules, resulting in a gel state after self-assembly. The collagen fibers obtained by the special salting-out process have fewer water molecules between the collagen molecules in the fibers due to the dehydration effect of salting-out. In this state, self-assembly is performed again, and the molecules are rearranged in a high aggregation state. The obtained state is still a fiber state, not a gel state, with a higher concentration, stronger mechanical strength, and better resistance to enzymatic hydrolysis.
[0027] Furthermore, in the step S1, the low temperature is 8-15°C.
[0028] Furthermore, in the step S1, the stirring speed is 80-150 rpm; the directional stirring is greater than 24 h, until the collagen is salted out to the maximum extent.
[0029] In step S1, the collagen salting out precipitation is fibrous. As the stirring time increases, the fibers gradually connect and become longer. Keeping the temperature low is to ensure that the collagen molecular structure is stable during the salting out process and will not be denatured by heat. The salting out process requires that sodium chloride be dissolved into a saturated solution and then slowly poured in. If sodium chloride crystals are directly added for salting out, the collagen in the solution will be rapidly precipitated around the crystals, and the obtained collagen salting out precipitation is blocky rather than fibrous. The high-concentration sodium chloride solution is slowly poured in a uniform directional stirring process, in order to allow the collagen in the solution to precipitate after lateral shear force exists, so that the collagen precipitation can be entangled in a directional manner into long and thin fibers. As the stirring time increases, collagen is further precipitated and the fiber growth becomes longer. The purpose of using saturated sodium chloride solution in step S1 is to make the added solution system as small as possible to avoid too much final solution system; if the concentration of the sodium chloride solution used is too low, the volume of the added salt solution will be too large, the collagen concentration of the solution will be diluted too much, the precipitation efficiency of the collagen will deteriorate and the mechanical properties will be poor; the salting-out process requires slow addition of saturated sodium chloride solution, appropriate stirring speed and low temperature, otherwise it will be impossible to obtain fibrous precipitation and collagen fibers with good mechanical properties.
[0030] Furthermore, the dispersant in step S2 includes any one or more combinations of sorbitol, glycerol, glucose, proline, glycine, and quaternary ammonium salts.
[0031] Furthermore, in step S2, the mass ratio of collagen to dispersion liquid is 1:15-1:30.
[0032] The stirring time in step S1 needs to be greater than 24 h and the solution system is re-transferred to ensure that the collagen in the solution is completely salted out, to prevent dissolved collagen molecules, and to avoid the remaining collagen molecules in the solution from self-assembling into gel after the solution system is adjusted to a state suitable for the self-assembly of collagen molecules in the next step, thereby affecting the appearance of the precipitated collagen fibers. The addition of a dispersant can prevent collagen fibers from agglomerating during the self-assembly process.
[0033] In step S3, the solution needs to be adjusted to neutral first, and then the sodium chloride concentration is adjusted. If the sodium chloride concentration is diluted to 0.1-0.3 M first, the precipitated fibrous collagen will be redissolved, and the neutral collagen solubility is the lowest. Therefore, the pH of the system needs to be adjusted to neutral before diluting the sodium chloride. In this step, the fibrous collagen stirred and precipitated is in a physiological state to achieve collagen self-assembly, further enhance the stability of the fibrous collagen, maintain the fibrous state of the collagen, and achieve the strengthening of the collagen fiber strength and stability without adding a cross-linking agent. The obtained fibrous collagen material has good mechanical strength and resistance to enzymolysis.
[0034] In a second aspect, the present application provides a collagen fiber material:
[0035] The material microstructure of the collagen fiber material is fibrous, and the collagen concentration is 30-75 mg / mL.
[0036] The collagen fiber material can be freeze-dried to obtain a powdered fiber material.
[0037] In a third aspect, the present application provides the application of collagen fiber materials in medical filling materials and implant materials. Beneficial Effects
[0038] 1. In the collagen fiber material and preparation method of the present application, mannitol is added as a dispersant during the salting out process; further, a high concentration sodium chloride solution is slowly added under low temperature and uniform directional shear stirring to form an elongated collagen fiber material during the stirring process; then the fiber intermediate is transferred to a newly configured solution, the acidic high salt concentration can maintain the precipitation state of the fiber collagen, and the dispersant can maintain the optimal dispersion state of the fiber collagen; then the solution environment is regulated so that the fiber collagen after thorough salting out is in a physiological simulation state for self-assembly; the polyol dispersion, salting out, dispersion liquid re-dispersion, and physiological simulation state self-assembly in the present application are mutually compatible, and the salt concentration and pH value of each step are strictly controlled, so that the collagen is prevented from rapidly salting out and agglomerating into a mass, and the fiber collagen is stably precipitated without adding a cross-linking agent, and the obtained collagen has high mechanical strength and resistance to enzymatic hydrolysis.
[0039] 2. The prepared microfiber material has the unique triple helix structure of collagen and is not modified by side chains, which ensures the biological activity of the material. The concentration of the fiber collagen material is 30-75 mg / ml, and it has high mechanical strength and resistance to enzymatic hydrolysis.
[0040] 3. The prepared collagen material has a fibrous structure. Compared with collagen salting-out precipitation, it does not require the addition of any cross-linking agent. It has higher mechanical strength and resistance to enzymatic hydrolysis and can be used for medical filling, implantation, and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1The collagen precipitation state in the salting-out process of step S1 of the preparation method of Examples 1, 2 and Comparative Examples 1-3;
[0042] Figure 2 The appearance of the collagen material obtained by the preparation methods of Examples 1, 2 and Comparative Examples 4-7;
[0043] Figure 3 It is the stacked state of the collagen material obtained by the preparation method of Examples 1, 2 and Comparative Examples 4-7 after being pushed out by a 30 g syringe needle;
[0044] Figure 4 It is the SEM image of the surface microstructure of the collagen material obtained by the preparation method of Examples 1, 2 and Comparative Examples 6, 7. DETAILED DESCRIPTION
[0045] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0046] Embodiment 1, a collagen fiber material and a preparation method thereof, comprising the following preparation steps:
[0047] S1: Add mannitol to an acidic collagen solution with a concentration of 3 mg / mL and pH 3, and stir for 30 min to form a mixed solution; the mannitol concentration in the mixed solution is 40 mg / mL; then slowly add a saturated sodium chloride aqueous solution to the mixed solution, and the final sodium chloride concentration in the solution is 1.2 M. Control the temperature at 8 °C, set the directional stirring speed to 80 rpm, and stir for 24 h.
[0048] S2: Prepare a new 1M sodium chloride aqueous solution, add sorbitol to a concentration of 40 mg / mL, and adjust the pH of the solution to 3 with hydrochloric acid to obtain a dispersion; take out the fiber filaments after salting out in step S2, and transfer them to the dispersion at a liquid ratio of 1:20.
[0049] S3: 3 M sodium hydroxide solution was slowly added under static state to adjust the pH of the system obtained in step S2 to 7.5; water was added to dilute the sodium chloride concentration of the system to 0.1 M, the material was heated to 37 °C, and maintained at rest for 2 h.
[0050] S4: The fibrous collagen is taken out and washed with physiological saline for multiple times to obtain a collagen material with a fibrous structure.
[0051] Embodiment 2, a collagen fiber material and a preparation method thereof, comprising the following preparation steps:
[0052] S1: Add sorbitol to an acidic collagen solution with a collagen concentration of 8 mg / mL and pH 3, and stir for 30 min to form a mixed solution; the sorbitol concentration in the mixed solution is 40 mg / mL; slowly add a saturated sodium chloride aqueous solution to the mixed solution, and the final sodium chloride concentration of the solution is 2.5 M. The temperature is controlled at 15 °C, the directional stirring speed is set to 150 rpm, and the mixture is stirred for 24 h.
[0053] S2: Prepare a new sodium chloride aqueous solution with a concentration of 1 M, add glycerol to make its concentration 20 mg / mL, adjust the pH of the solution to 3 with hydrochloric acid, and obtain a dispersion; take out the fiber filaments after salting out in step S2, and transfer them to the dispersion with a liquid ratio of 1:20.
[0054] S3: Slowly add 3 M sodium hydroxide solution while standing to adjust the pH of the system obtained in step S2 to 6.5; add water to dilute the sodium chloride concentration of the system to 0.3 M. Heat the material to 37 °C and keep it standing for 2 h.
[0055] S4: The fibrous collagen is taken out and washed with physiological saline for multiple times to obtain a collagen material with a fibrous structure.
[0056] Comparative Example 1, a collagen fiber material and a preparation method thereof, is different from Example 1 in that no dispersant is added in step S1.
[0057] Comparative Example 2, a collagen fiber material and a preparation method thereof, is different from Example 1 in that a dispersant and sodium chloride are added simultaneously in step S1 for salting out; the specific operation of step S1 is as follows:
[0058] Saturated sodium chloride aqueous solution and a mixture of mannitol in the same amount as in Example 1 were slowly added to the acidic collagen solution at the same time, and the final sodium chloride concentration in the solution was 1.2 M. The temperature was controlled at 8° C., the stirring speed was set at 80 rpm, and the mixture was stirred for 24 h.
[0059] Comparative Example 3, a collagen fiber material and a preparation method thereof, is different from Example 1 in that the sodium chloride concentration of the final solution in step S1 is 0.8 M.
[0060] Comparative Example 4, a collagen fiber material and a preparation method thereof, differs from Example 1 in that no dispersant is added to the newly prepared sodium chloride aqueous solution in step S2.
[0061] Comparative Example 5, a collagen fiber material and a preparation method thereof, differs from Example 2 in that, during the self-assembly process of step S3, the sodium chloride concentration of the system is first diluted to 0.3 M, and then the pH of the system is adjusted to a neutral pH of 6.5.
[0062] Comparative Example 6, a collagen fiber material and a preparation method thereof, is different from Example 2 in that the pH value is adjusted to 5 during the self-assembly process in step S3.
[0063] Comparative Example 7, a collagen fiber material and a preparation method thereof, is different from Example 2 in that the salt concentration of the self-assembly process in step S3 is adjusted to 0.5 M.
[0064] Performance measurement:
[0065] 1. Collagen precipitation state during salting out process, see Figure 1 :
[0066] Figure 1 This is the appearance of collagen precipitation after salting out for 24 hours in step S1. Example 1 and Example 2 are salting out in the presence of a dispersant, and the concentration of sodium chloride for salting out is 1.2 M and 2.5 M. As can be seen from the figure, the collagen is precipitated in a fibrous state, and the fiber filaments grow and entangle on the stirring rod as the stirring proceeds. In Comparative Example 1, no dispersant is added, and salting out is directly performed; the collagen is mainly precipitated in an uneven agglomerate state, without a fibrous appearance. In Comparative Example 2, a dispersant and a sodium chloride solution are added at the same time for salting out, and the collagen presents an uneven block precipitation without a fibrous appearance. The concentration of sodium chloride for salting out used in Comparative Example 3 is 0.8 M. Since the salting out concentration is insufficient in the presence of a dispersant, no collagen is precipitated, and the system is in a solution state.
[0067] 2. Final material appearance
[0068] (1) Collect the final collagen material after washing with saline solution, and the appearance of each Figure 2 :
[0069] The final materials obtained in Example 1 and Example 2 are milky white solids. The materials have good stacking properties. After being placed for 1 hour, the shapes do not change and do not collapse.
[0070] In comparative example 1, no dispersant was added in step S1, and the precipitated collagen was block-like, uneven masses, not fibrous.
[0071] Comparative Example 2: In step S1, a dispersant and sodium chloride were added simultaneously for salting out, and the precipitated collagen was block-like, non-fibrous.
[0072] In comparative example 3, the sodium chloride concentration of the final solution in step S1 was 0.8 M, which was not high enough and no collagen was precipitated.
[0073] In comparative example 4, no dispersant is added to the newly configured sodium chloride aqueous solution in step S2; without using a dispersant, self-assembly cannot form a fibrous collagen material, but an overall turbid gel, with collagen fibers aggregated into a gel; the final material obtained in comparative example 4 is a transparent gel-like collagen, which quickly leveled during placement, had no stacking plasticity, and had poor mechanical properties. This is because no dispersant was used in the self-assembly process, resulting in further rapid self-assembly between the fibrous collagen precipitated in the previous process, resulting in a large amount of entanglement between the original fibers, and the collapse of the high-concentration fiber structure.
[0074] In comparative example 5, during the self-assembly process of step S3, the sodium chloride concentration of the system was first diluted to 0.3 M, and then the pH of the system was adjusted to a neutral 6.5, and the fibrillar collagen precipitated and dissolved, and finally formed a transparent jelly-like gel with good material fluidity and poor stacking mechanical properties. This is because the sodium chloride concentration of the system was first diluted during the collagen self-assembly process, and the low concentration of sodium chloride in the acidic state can promote the dissolution of collagen, resulting in the precipitation and dissolution of the collagen fibers precipitated by the previous process into a collagen solution, and then self-assembled in a solution state, and the obtained collagen material was in a gel state with a low concentration and poor mechanical properties.
[0075] The fiber collagen materials obtained in Comparative Examples 6 and 7 are milky white, and their concentrations are lower than those in the examples, and the subsequent stacking performance and mechanical properties are also poor. This is because the self-assembly pH of Comparative Example 6 is 5, and the degree of self-assembly is weak, resulting in weak interactions between fibers. The self-assembly salt concentration adjusted in Comparative Example 7 is 0.5 M. Due to the high salt concentration, the salt dissolution effect causes the fiber-state collagen obtained by the salting-out process to precipitate out with a slight tendency to disperse and dissolve, so the mechanical strength of the obtained material is poor.
[0076] (2) The stacking state of each group of materials after being pushed out by a 30 g syringe needle is as follows: Figure 3 :
[0077] After being pushed, the examples 1 and 2 present a continuous wire drawing state, showing good stacking state and mechanical properties. The comparative examples 4 and 5 are gel-like and have poor stacking properties; the stacking and mechanical properties of the comparative examples 6 and 7 are worse than those of the examples.
[0078] 3. Determination of the concentration of the final obtained material
[0079] After digestion of the prepared material, the concentration of hydroxyproline in the sample was determined. Hydroxyproline is a characteristic amino acid unique to collagen molecules, and the collagen concentration of the material can be converted according to the concentration of hydroxyproline. Three parallel samples were set for each group of samples, and the concentration results of each sample were obtained as shown in Table 1:
[0080] Table 1. Collagen concentrations of materials obtained using Examples 1-2 and Comparative Examples 4-7
[0081]
[0082] As can be seen from the data in the above table, the sample concentrations of Example 1 and Example 2 are both greater than 80 mg / mL. This is because the collagen fibers obtained by the special salting-out process are essentially the aggregation state of a large number of collagen molecules. Due to the dehydration effect of salting-out, the moisture between the collagen molecules in the fiber is less. In this state, self-assembly is performed again, and the molecules are rearranged in a high aggregation state. The material obtained is in a fiber state rather than a gel state, and the concentration is higher. The final fiber collagen material can be diluted to 30-75 mg / mL for in vivo implantation and filling. In Comparative Example 4, since no dispersant was added to the system solution during the self-assembly process, rapid self-assembly occurred laterally between the fibers, resulting in the disappearance of the original fiber state, and the material presented a turbid gel state with a low concentration. In Comparative Example 5, since the salt concentration of the system was diluted first, the precipitation state of the original fiber collagen was destroyed, and the low concentration of salt dissolution caused the self-assembly to form a gel, and the collagen concentration was insufficient. In Comparative Examples 6 and 7, since the self-assembly conditions of the fibers were not the optimal physiological state for collagen self-assembly, the degree of self-assembly was reduced, and the fiber strength of the obtained material was weakened and the concentration was low.
[0083] 4. Surface microstructure
[0084] Figure 4 The following are SEM images of the microscopic morphology of the collagen fiber surface obtained by the preparation methods of Examples 1 and 2 and Comparative Examples 6 and 7 at the same magnification (20,000 times). Figure 4 It can be seen that the surface microstructures of Examples 1 and 2 are obviously filaments, and there are close connections between the filaments, with obvious D-periodic structures of collagen fiber tissue. It shows that the obtained collagen material is in a fibrous state, and the self-assembly occurring on the fiber surface forms a characteristic D-periodic structure. There is a close connection between the fibers, so that the obtained fiber collagen material has stronger resistance to enzymatic hydrolysis and mechanical properties. The surface microstructure of Comparative Example 6 presents a continuous and smooth film-like shape, and no obvious D-periodic structure is seen. It shows that under the state of pH 5, the collagen fibers originally precipitated did not undergo obvious self-assembly; the material dispersed and dissolved the fibers within 2 h after heating in step S3, resulting in the deterioration of the mechanical properties and resistance to enzymatic hydrolysis of the material. The comparative example 7 also shows a continuous and smooth plane, and a small amount of filamentous precipitation can be seen, but the D-periodic structure after self-assembly is not seen on its surface. It shows that the sodium chloride concentration of 0.5 M has a salt-dissolving effect, which causes the collapse and dissolution of the surface of the originally precipitated fibrous collagen, and the mechanical properties are weakened.
[0085] 5. Determination of the enzymatic resistance of the final material
[0086] The enzymatic hydrolysis resistance of the prepared collagen material was determined by in vitro enzymatic hydrolysis experiments. Take the prepared collagen material and dilute it with physiological saline to the same collagen concentration of 25 mg / mL. Take 2 g of the sample and implant it into a 5 mL centrifuge tube, add 3 mL of type I collagenase with an activity of 20 U / mL, seal the centrifuge tube and place the sample in a constant temperature water bath at 37 °C for incubation for 5 h. After the incubation, remove the centrifuge tube, centrifuge at 3000 speed for 5 min, determine the hydroxyproline content of the supernatant of each group of samples, and obtain the collagen concentration by conversion. The collagen content in the supernatant is judged as the degraded collagen, and the degradation rate of the material in 5 h is calculated to judge the material's resistance to enzymatic hydrolysis. The results of the enzymatic hydrolysis resistance of each group of samples are shown in Table 2 below:
[0087] Table 2. Degradation rates of materials obtained using Examples 1-2 and Comparative Examples 4-7
[0088]
[0089] As can be seen from the above results, Example 1 and Example 2 are fibrous collagen materials, and their degradation rate is low, indicating that the material has a strong resistance to enzymolysis. This is because the embodiment has obtained a fibrous collagen material through a special salting-out process, and the high-concentration fibrous collagen material is further self-assembled on the surface in the presence of a dispersant, and the fibrous collagen is further reinforced, resulting in a higher mechanical strength of the material, a denser fiber structure, and a reduced contact probability of type I collagenase and collagen molecules, which greatly improves the resistance to enzymolysis of the material. Comparative Example 4 does not contain a dispersant, and during the material self-assembly process, a large amount of adhesion occurs between the fibers, resulting in the original fiber structure stability becoming poor, and the resistance to enzymolysis of the material is reduced. Comparative Example 5 is due to the solution being diluted first, resulting in the original fiber precipitation state collagen having a salt-dissolving effect, and the collagen after dissolution is similar to the conventional solution state collagen self-assembly, and due to the presence of a large amount of water molecules between the collagen molecules, a gel is formed after self-assembly. The concentration of collagen gel is low, and the gap between the molecular structure is large, and type I collagenase can quickly contact the collagen molecules and rapidly degrade them. In Comparative Examples 6 and 7, since the self-assembly conditions of the fibers are not the optimal physiological state for collagen self-assembly, the degree of self-assembly is reduced, and the fiber collagen material is not dense enough, resulting in insufficient resistance to enzymatic hydrolysis.
[0090] 6. Determination of viscoelastic properties:
[0091] Elastic modulus and viscous modulus are two important physical properties that describe the response of materials to external forces. They measure the rigidity (elastic behavior) and rheology (viscous behavior) of materials under force, respectively. Materials with high elastic modulus are "harder" and less likely to deform; materials with low elastic modulus are "softer" and more likely to deform. The higher the viscous modulus of a material, the poorer its fluidity, the slower it deforms, and the stronger its energy dissipation capacity. Therefore, the higher the elastic modulus and viscous modulus, the stronger the resistance to external force deformation and mechanical properties of fibrous collagen, and the better its support.
[0092] Experimental methods:
[0093] Take 1 g of the final sample and plot the elastic modulus G' and viscous modulus of the sample at 25 °C in the range of 0.05-10 Hz according to the rheometer operating procedures. G'' The logarithm of the frequency is plotted, and the values of the viscous modulus and elastic modulus at 1 Hz are given. Each group of samples is measured three times in parallel. The test results are shown in Table 3.
[0094] Table 3. List of viscous modulus and elastic modulus of materials obtained using Examples 1-2 and Comparative Examples 4-7
[0095]
[0096] According to the above experimental results, the elastic modulus and viscous modulus of Examples 1 and 2 are both above 5000 Pa and 1900 Pa, showing better rigidity and resistance to energy dissipation than the comparative examples, so the mechanical properties are stronger and the filling performance is better. In Comparative Example 4, since no dispersant was used, a large amount of adhesion occurred between the fibers during the self-assembly process of the material, resulting in poor stability of the original fiber structure, and thus poor mechanical properties; in Comparative Example 5, due to the fiber salt dissolution phenomenon caused by dilution, collagen self-assembled in the form of a single molecule, resulting in a large number of water molecules between the formed gel. Due to the increase in the water content of the material, its elastic modulus and viscous modulus were greatly reduced, and the mechanical stacking properties of the material deteriorated; and in Comparative Examples 6 and 7, since the self-assembly conditions of the fibers were not the optimal physiological conditions for collagen self-assembly, the degree of self-assembly was reduced, the fiber collagen material was not dense enough, and its elastic modulus and viscous modulus values were low, and the mechanical properties were poor.
[0097] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a collagen fiber material, characterized in that: The method comprises the following preparation steps: S1: adding polyol to the acidic collagen solution and stirring to form a mixed solution, wherein the concentration of the polyol in the mixed solution is 35-45 mg / mL; Then, a saturated sodium chloride solution is slowly added to the mixed solution for salting out while maintaining uniform directional stirring, and the final sodium chloride concentration in the solution is 1.2-2.5 M, and the salting out process is carried out at a low temperature; The polyol is mannitol or sorbitol; S2: taking the collagen precipitated in step S1 and transferring it to a dispersion solution, wherein the dispersion solution is a 1-1.2 M sodium chloride aqueous solution to which 20-40 mg / mL of a dispersant is added, and the pH is adjusted to 3-4 to obtain a mixed solution; The dispersant is sorbitol or glycerol; S3: Use an alkaline solution to adjust the pH of the solution obtained in step S2 to 6.5-7.5; then add water to the system, dilute the sodium chloride concentration to 0.1-0.3 M, heat the water bath to 37-39°C, and let it stand for 2-3 hours; S4: Take out the precipitated collagen fibers, wash with physiological saline, and concentrate them after centrifugation to obtain the final collagen fiber material.
2. The method for preparing a collagen fiber material according to claim 1, characterized in that: The pH value of the acidic collagen solution in step S1 is 2-4.
3. The method for preparing a collagen fiber material according to claim 1, characterized in that: The collagen in the acidic collagen solution in step S1 includes any one or more combinations of type I collagen, type II collagen, and type III collagen; The concentration of collagen in the acidic collagen solution is 3-10 mg / mL.
4. The method for preparing a collagen fiber material according to claim 1, characterized in that: The low temperature in step S1 is 8-15°C.
5. The method for preparing a collagen fiber material according to claim 4, characterized in that: In the step S1, the stirring speed is 80-150 rpm; the directional stirring is greater than 24 h, until the collagen is salted out to the maximum extent.
6. The method for preparing a collagen fiber material according to claim 1, characterized in that: In the step S2, the mass ratio of collagen to dispersion liquid is 1:(15-30).
7. The collagen fiber material obtained by the method for preparing the collagen fiber material according to any one of claims 1 to 6, characterized in that: The material microstructure of the collagen fiber material is fibrous, and the collagen concentration is 30-75 mg / mL.
8. Use of the collagen fiber material as claimed in claim 7 in medical filling materials and implant materials.
Citation Information
Patent Citations
Technique for preparing sponge produced from collagen
CN100444902C
Method for forming fiber through self-assembly of aquatic collagen
CN104073902A
Glutaraldehyde cross-linked collagen fiber as well as preparation and application thereof
CN118241482A
process for preparing acid solutions of reconstitutable collagen
BE608261A
Microfluidic extrusion
CA3128219A1